Proactive inter-datacenter multicast with realtime and bulk transfers - Dolati, Mahdi; Ghaderi, Majid; Khonsari, Ahmad (Proceedings of the International Symposium on Quality of Service, 2019)
In content distribution networks, a key objective is the efficient utilization of the network that interconnects geographically distributed datacenters. This is a challenging problem due to vastly different characteristics and requirements of bulk and realtime transfers that share the interconnection network. Bulk transfers aim at delivering a copy of a usually large file to multiple datacenters before a deadline, while realtime transfers are absolutely delay-intolerant with unsteady and dynamic demands. In this paper, we consider the problem of multicasting deadline-critical bulk transfers in an inter-datacenter network in the presence of unknown and fluctuating demand by realtime transfers. Specifically, we develop a joint admission control and routing algorithm called PMDx, which anticipates future realtime demands and proactively reserves just the right amount of network resources in order to serve future realtime transfers without adversely affecting network utilization or bulk transfer deadlines. We show that the PMDx algorithm is a 2/δ-approximation with probability 1 - ϵ, and runs in polynomial time proportional to ln(1/ϵ)/(1 - δ)2, for 0 < δ,ϵ < 1. We also provide extensive model-driven simulation results to study the behaviour of our algorithms in real world network topologies. Our results confirm that PMDx is very close to the optimal, and improves the utilization of the network by 14% compared to a recently proposed algorithm.